Trophic Status In Joto Reservoir, Lamongan - Norma Aprilia Fanni; Fuquh Rahmat Shaleh (University of Prof. Dr. Hazairin, SH, 2021)
Joto Reservoir is a reservoir in Lamongan Distric which is commonly used by local people for their daily activities. In addition, the reservoir water flow is also used for fishing and agricultural activities. In the management of a sustainable and sustainable waters, basic information about the level of fertility of the waters is needed for proper use. This study aims to determine the water quality and fertility status of the waters in the Joto Reservoir, Lamongan Distric. The data collection method used purposive random sampling at three stations, namely the inlet, middle, and outlet sections. Determination of water fertility status based on calculations using the Carlson Trophic State Index (TSI). Water sampling was carried out at intervals of once a month for 3 months from December 2020 to February 2021. The parameters observed included temperature, brightness, pH, salinity, dissolved oxygen (DO), nitrate, total phosphate, chlorophyll-a. The results showed that the fertility status of the Joto Reservoir waters in December 2020 - February 2021 based on the Carlson TSI was included in the category of hypereutrophic waters with a value of 74. It is recommended to carry out further research in different seasons to determine the status of water fertility in the dry season.